# How do you use the chain rule to differentiate #y=cos(2x+3)#?

By signing up, you agree to our Terms of Service and Privacy Policy

To differentiate ( y = \cos(2x + 3) ) using the chain rule:

- Identify the outer function, which is ( \cos(u) ), where ( u = 2x + 3 ).
- Differentiate the outer function with respect to its inner variable ( u ), which is ( \frac{d}{du} \cos(u) = -\sin(u) ).
- Differentiate the inner function with respect to the variable ( x ), which is ( \frac{d}{dx} (2x + 3) = 2 ).
- Apply the chain rule by multiplying the derivatives from steps 2 and 3: ( \frac{dy}{dx} = -\sin(u) \cdot 2 ).
- Replace ( u ) with ( 2x + 3 ) to get the final derivative: ( \frac{dy}{dx} = -2\sin(2x + 3) ).

By signing up, you agree to our Terms of Service and Privacy Policy

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7